2021
DOI: 10.1097/won.0000000000000734
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Acquired Pressure Injuries and Acute Skin Failure in Critical Care

Abstract: PURPOSE The purpose of this study was to examine clinical characteristics and risk factors for critically ill patients who develop pressure injuries and identify the proportion of validated unavoidable pressure injuries associated with the proposed risk factors for acute skin failure (ASF). DESIGN: Retrospective case-control comparative study. SUBJECTS AND SETTING: The sample comprised adult critically ill p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 22 publications
2
24
1
Order By: Relevance
“…The incidence of PIs found in the CG of the present study is similar to the values presented by other authors [ 1 , 2 ]. This high incidence indicates the lack of effectiveness of the current PI prevention strategies recommended in the guidelines, demonstrating the need to study new tools, such as NMES [ 3 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The incidence of PIs found in the CG of the present study is similar to the values presented by other authors [ 1 , 2 ]. This high incidence indicates the lack of effectiveness of the current PI prevention strategies recommended in the guidelines, demonstrating the need to study new tools, such as NMES [ 3 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Critically ill patients are at a high risk of developing a pressure injury (PI) [ 1 , 2 ]. PIs can occur as a result of intense and/or prolonged pressure combined with shear forces [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using interpersonal team strategies, nurse-driven protocols, and a standardized catheter care bundle, catheter-associated urinary tract infections were decreased by greater than 50% across a 2-year period, resulting in cost avoidance of $31 000 per case. An analysis of pressure injuries The novel, institutionally copyrighted instrument enabled clear identification of prevention opportunities in the organization and a mechanism to further expand scientific knowledge in the literature 20,21 Abbreviations: CLABSI, central line-associated blood stream infection; CPOT, Critical Care Pain Observation Tool; EHR, electronic health record.…”
Section: Discussionmentioning
confidence: 99%
“…5 We assert that the rise of HAPI rates reported by the AHRQ indicates the complexity of PI prevention and evidence indicating that not all PIs are preventable or avoidable. 3 For example, Pittman and colleagues 3 reported that more than 40% of PIs in the critical care setting were unavoidable, indicating that approximately 60% were avoidable. As a result, hospitals must increase their attention to PI that can be prevented.…”
Section: Introductionmentioning
confidence: 99%